Expression of miR-199a, lum and ets2 in benthic and pelagic Arctic charr morphs at developmental stage 200τ - Ligthart, Kate, 1992- (2014)
MiRNAs play an important role in development by regulating gene expression. They are recruited to RISC complexes, which bind to target mRNAs. This interaction causes silencing of the target mRNAs by repressing translation or by initiating degradation. In lake Þingvallavatn there are four morphs of Arctic charr that are very different in morphology and their feeding apparatus. The different morphs of Arctic charr have different levels of miRNA gene expression during their embryonic development. MiR-199a is one of these miRNAs and it and its putative targets, lum and ets2, were investigated in the large benthic (LB) morph at developmental stage 200 τ. WISH staining was used followed by cryosectioning to gain insight in the cellular expression of miR-199a, lum, and ets2. Expression of miR-199a and ets2 was found in the pharyngeal arches outside of the cartilage while the expression of lum was found inside of the cartilage. Thus, ets2 is likely to be a target of miR-199a whereas lum is probably not. Expression patterns of miR-199a, lum, and ets2 were also analysed in pelagic planctivorous (PL) charr at the same developmental stage (200 τ). Similar expression was found in PL as in LB. Furthermore, a computational approach was used to find putative targets for miR-206 resulting in 36 possible targets.